ASIA AS A KNOWLEDGE PRODUCER IN THE WORLD - E. V. Koldunova (Сравнительная политика, 2016)
For the past few years many IR scholars focused mainly on the question in what way the rise of Asia could infl uence the post-bipolar world order and world economic system. However with all due attention to the international economic and political transformations, which followed Asia’s rise, IR studies paid little attention to the gap between rising economic and to some extent political role of Asia in the world system and still Western-dominated production of new technological and humanitarian knowledge. This article analyses in the comparative way three efforts to bridge this gap. The fi rst one is an effort to build up an indigenous discourse about Asia. The second refers to the discussion about the possibilities to develop a non-Western IR theory. The third one is connected with the rise of Asian think tanks and universities.